Margarina a base de oleogel de azeite de oliva: caracterização e estabilidade - Barbosa, Bárbara Viana Lessa (2021)
Studies with oleogels, viscoelastic materials composed of structuring agents and a liquid phase aid, has been growing a lot, due to its future promising in several fields. In the food industry, its advance has been encouraged due to its great possibilities of applications, as well as to replace the trans and saturated fats, related to health problems. The use of oils with a good lipid profile, such as extra virgin olive oil, is a good alternative for the composition of oleogels. Thus, the present study aims to elaborate and characterize margarines made with extra virgin olive oil, coconut oil, starch and beeswax in different concentrations. To this end, pre-tests were carried out in order to trace the concentrations of the independent variables (olive oil/coconut oil, beeswax and starch) for the preparation of the oleogel, followed by the manufacture of the three different formulations of margarines. The margarines, together with a commercial sample (standard), were analyzed for thermal and oxidative stability, microstructure and color for three months, every 30 days, from time zero to 90 days. Also performed the differential exploratory calorimetry analysis was once concluded during data collection. Commercial margarine requires a lower temperature to merge and showed about 4ml of oil exudation, given the temperature fluctuation. The proposed formulations with oleogel, in addition to requiring a greater melting temperature range to melt, demand less energy, on average 4,45J/g. In lipid oxidation, although standard margarine had smaller parameters when compared to other formulations, these are within the limits despite differences found between the standard and the other formulations, however, the same are within the limits established for olive oil. There was also a significant difference in color, since the oleogel tended the samples to a more greenish color when compared to the commercial one and, in the microstructure, the commercial margarine presented smaller water bubbles and distributed more evenly in the space. Thus, margarines elaborate with oleogel of olive oil proved to be viable, with a probable need for some adjustments and confirmation of sensory acceptance. Considering the interest of consumers for innovation and healthiness in foods, margarine based on olive oil oleogel can be an interesting alternative due to the nutritional benefits of olive oil.